The FOSTERING SMALL BUSINESS ENTREPRENEURSHIP IN TANZANIA - Mtuka, Ditrick Dismas (International Journal of Economics, Business, and Entrepreneurship, 2020)
Small Business Entrepreneurship has been seen as a hub in generating income for the majority of urban dwellers with no formal paid employment. In Tanzania, entry into small business entrepreneurship is usually not seen as a problem. One can start small business at any time and in any place. However, the development of this informal sector has been profoundly characterized by two parallel phenomena which are perhaps contradictory in character. This has led to the proliferation and mushrooming of small businesses most of which are in the form of petty trading, generally everywhere in the urban centres. Drawing on research findings, the present paper challenges the possibility of reducing poverty in Tanzania using the strategy of developing the small business entrepreneurship under the situation where there is an increasing level of petty crime and bureaucratic hurdles. It is argued and indeed, concluded that if the present intricate and controversial situation surrounding small business is not reversed, if not brought to rest, the development is on slippery slope. The option suggested to tame the conundrum includes, developing discourse portfolio between small traders and bureaucratic authority and authorities formulating policies that can promote development of small business entrepreneurship.